Perancangan Panel Pompa 2 HP dengan Metode Pengasutan Direct On Line di PT. Tiga Kreasi Indonesia - Arjuna Fikri Tri Firmansyah; Bagus Dwi Cahyono (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
Electrical energy is the main energy required for electrical equipment, to distribute this electrical energy requires an electrical panel. PT. Tiga Kreasi Indonesia is a company engaged in the manufacture of electrical panels with one of its products being a 2 HP pump panel which functions to activate and control a pump. This research uses observation method and literature study. The data collection method in this study was a direct observation system and literature study. The design process for the 2 HP pump panel has several stages, such as preparing the panel box first to place the appropriate components in the panel box construction drawings, then preparing a single line diagram and wiring drawings to serve as a reference to be connected between components, then preparing the components used, then arranging the components in the panel box match those in the panel box construction, then they are connected between the components according to the reference picture in the single line diagram and wiring diagram. Then simulate whether the DOL circuit is functioning, and the result is that the DOL circuit is functioning.